Children’s Spontaneous Gestures Reflect Verbal Understanding of the Day/Night Cycle - Gaudreau, Caroline M.; Anggoro, Florencia K.; Jee, Benjamin D. (Frontiers in Psychology, 2020)
Understanding the day/night cycle requires integrating observations of the sky (an Earth-based perspective) with scientific models of the solar system (a space-based perspective). Yet, children often fail to make the right connections, and resort to nonscientific intuitions—e.g., the Sun moving up and down—to explain what they observe. The present research explored whether children’s gestures indicate their conceptual integration of Earth- and space-based perspectives. We coded the spontaneous gestures of 85 3rd-grade children in U.S. public schools (Mage=8.87 years) as they verbally explained the overall cause of the day/night cycle, the cause of sunrise, and the cause of sunset after receiving science instruction as part of a prior study. We focused on two kinds of gestures: those reflecting the Sun’s motion across the sky, and those reflecting the Earth’s axial rotation. We found that participants were more likely to produce Earth rotation gestures for a topic they explained more accurately (the overall cause of the day/night cycle), whereas Sun motion gestures were more common for topics they explained less accurately (the causes of sunrise and sunset). Further, participants who produced rotation gestures tended to provide more accurate verbal explanations of the overall cause. We discuss how gestures could be used to measure—and possibly improve—children’s conceptual understanding, and why sunrise and sunset may be particularly difficult topics to learn.